Evaluation of chitosan based pretreatment for cotton and linen dyeing with direct dyes and reactive dyes - Mohammad Toufiqul Hoque; Tian Benrui; Thomas Grethe; Boris Mahltig (Communications in Development and Assembling of Textile Products)
Cellulosic materials like cotton and linen are excellent textile substrates for dyeing with reactive and direct dyes. Due to their cellulosic nature, cotton and linen exhibit good affinity towards direct and reactive dyes. This good affinity is the reason for good washing and rubbing fastness. Chitosan is a bio-based polymer gained by the deacetylation of chitin. In contrast to cellulose, chitosan exhibits also amino functional groups. The purpose of this paper is to evaluate if a chitosan based pretreatment of cotton and linen can lead to different dyeing properties. After different chitosan based pretreatments, the color properties are determined by CIEL*a*b* indices. The rubbing fastness in dry and wet conditions is measured. Even if in the actual study no positive effects were determined by pretreatment of chitosan, the determined results could be utilized in future research to develop other functional treatments of cotton and linen materials with implemented chitosan.